Studying the stability of an embankment over clay soil supported by stone columns - محمود علي; توفيق فياض (Latakia University Journal -Engineering Sciences Series, 2023)
Most of the numerical studies on stone columns are based on the unit cell concept. However, the impact of interactions between adjacent columns and between the columns and the surrounding soil has not been investigated thoroughly. In this study, the finite element software, PLAXIS-2D-V8.2, was used to simulate a stone column as a plane strain model. The key factors that were investigated included the diameter and c/c spacing of the stone columns, friction angle of the stone column material and stone column length. The emphasis of this parametric study was on the settlement improvement factor , since these are critical to the design of stone columns. The main findings of this study were that in the plane strain model, the settlement improvement factor ranged between 1.5 and 2.9 , which means that the settlement was improved more than twice.